THE ANALYSIS OF EFL STUDENTS’ ERRORS IN WRITING SKRIPSI - Hendraa Husnussalam (STKIP Siliwangi, 2016)
This study aims at analyzing EFL students’ errors in writing skripsi as the requirement to leave academy. The subjects of this study were thirty three skripsi-s written by the students who majored English language education in STKIP Siliwangi. The analysis of this study is based on the checklist of research articles elements in skripsi as proposed by Paltridge and Starfield (2007) who state that there are six moves to analyze the elements of skripsi. The results show that, based on each move of the checklist, there are only less than 50% of the students who can fulfill the requirements of each move item. Based on the facts, further research and development to resolve the problems are necessarily needed. We also need to reformulate a good standard of academic writing agreed by the institution through a book containing guidelines of how to make an appropriate skripsi-s. Key terms: analysis, students’ errors, skripsi